PERTANGGUNGJAWABAN NEGARA DALAM KEBOCORAN DATA PADA PLATFORM E-GOVERNMENT: ANALISIS HUKUM ADMINISTRASI ATAS KASUS SATU SEHAT DAN DPMPTSP ONLINE - Shafa Suhaila; Mutiara Andini; Oriza Satifa Wahyuni; M. Daris Alfi Putra Nurhadi; Muhammad Sahriadi Lubis (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Data breaches on digital public service platforms represent a critical phenomenon that tests the commitment of a constitutional state. This study analyzes state accountability under administrative law regarding data breach incidents on E-Government platforms, using case studies of Satu Sehat and DPMPTSP Online. The research employs a normative juridical method through case study and document analysis approaches. The findings indicate that although the legal framework for state accountability has been established under the Personal Data Protection Law (UU PDP) and its implementing regulations, its implementation has not fully realized the principle of legal certainty. The state’s responsibility as the data controller remains hindered by regulatory disparities, limited cybersecurity capacity, and incident response mechanisms that are slow and lack transparency. Forms of accountability that should be procedural and predictable such as the obligation of 72-hour notification, proportional administrative sanctions, and civil lawsuit mechanisms through the State Administrative Court (PTUN) are still not optimal in practice. This study concludes that strengthening state accountability requires regulatory harmonization, enhanced institutional capacity of the Personal Data Protection Authority (OPDP) and the National Cyber and Crypto Agency (BSSN), and standardized incident response protocols. Policy recommendations are directed toward reinforcing state accountability in protecting citizens' personal data in the digital sphere.